PENGARUH KOMPRES SERAI HANGAT TERHADAP PENURUNAN INTESITAS NYERI RHEMATOID ARTHRITIS - Rufaridah, Anne; Cumayunaro, Ayuro; Putri, Nesa Rahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Disease Rheumatoid arthritis causes chronic inflammation, as time goes by many cause various complaints such as pain, stiffness and muscle weakness resulting in decreased body function that disrupts activity and permanently causes damage to the joints. Complaints of pain usually arise when doing physical activity, pain also arises when resting is not related to the period of movement, or in the morning when you wake up. To reduce these complaints, one of the non-pharmacological management is a warm lemongrass compress. The purpose of this study was to determine the effect of warm lemongrass compress on reducing the intensity of Rheumatoid arthritis pain in the Parak Laweh Village in the Lubuk Begalung Health Center Work Area. This type of research is quasy experiment with the design of pre and post test control group design. Data collection was conducted in July 2018. The population was 10 people in the intervention group and 10 people in the control group. The pain intensity of the respondent before being compressed with warm lemongrass with 80% moderate pain and decreased to mild pain 70%. Statistical test results showed that there was an effect of warm lemongrass compress on decreasing the intensity of Rheumatoid arthritis pain. It is expected that health workers can socialize to the public about management to reduce the intensity of non-pharmacological Rheumatoid arthritis pain by compressing warm lemongrass.